2022
DOI: 10.5334/ijic.6418
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Governing Responsive Local Care Systems – Insights from a Scoping Review of Paramedics in Integrated Models of Care

Abstract: Introduction: Programs that fill gaps in fractured health and social services in response to local needs can provide insight on enacting integrated care. Grassroots programs and the changing roles of paramedics within them were analyzed to explore how the health workforce, organizations and governance could support integrated care. Methods: A study was conducted following Arksey and O’Malley’s method for scoping reviews, using Valentijn’s Rainbow Model of Integrated Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…It has been suggested that bureaucratic, command-and-control approaches to management and policy are partly why efforts to integrate services fail. Instead, the fostering of an enabling environment (Theme 2) would allow a more organic collaboration between professions and organisations [ 20 – 22 ]. It has long been maintained that co-ordinated service delivery relies on the integration of services at multiple levels [ 23 , 24 ], but the research is still evolving on how to do this in a way that would enable integration from the ground-up rather than imposing it from the top-down.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that bureaucratic, command-and-control approaches to management and policy are partly why efforts to integrate services fail. Instead, the fostering of an enabling environment (Theme 2) would allow a more organic collaboration between professions and organisations [ 20 – 22 ]. It has long been maintained that co-ordinated service delivery relies on the integration of services at multiple levels [ 23 , 24 ], but the research is still evolving on how to do this in a way that would enable integration from the ground-up rather than imposing it from the top-down.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a burgeoning evidence base for the role that community paramedics play in integrated, community care despite ongoing challenges with wider health system recognition of this expanded role 23. A recent scoping review examining factors that could support paramedics’ role within a responsive, local healthcare system noted the need for a cross-cutting service organisation 24. In our study, community paramedics were seen as connectors, linking residents with services and connecting themselves with other healthcare organisations in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated care and mental health were ranked highly. A recent scoping review of paramedics in integrated models of care 56 found that paramedics are often the link between acute and chronic care, play a key role in case finding within health systems, and can make considerable contributions to public health initiatives. Of the 137 documents included in the review, only eight originated from Australia and two from New Zealand, reiterating the need for research on the features, approaches, and outcomes of integration in pathways and models of care where Australian and New Zealand paramedics are involved.…”
Section: Clinical Pathways and Models Of Carementioning
confidence: 99%